Behind the screen: Commercial sex, digital spaces and working online. (May 2018) - Cunningham, Stewart; Sanders, Teela; Scoular, Jane; Campbell, Rosie; Pitcher, Jane; Hill, Kathleen; Valentine-Chase, Matt; Melissa, Camille; Aydin, Yigit; Hamer, Rebecca
Highlights: Exploration of how sex workers interaction with digital and online technology. Examine the shift to online sex work and importance of the internet. Discuss marketing strategies, the use of social media and personal websites to build brands. The impact of reviews on sex workers and their practice. Highlight some of the harms and dangers sex workers face using the internet as well as the benefits it affords.